Amyand’s hernia: a case report and review of the literature - Mendez, Andriana Teresa Cruz; Fuentes, Huber Diaz (International Journal of Research in Medical Sciences, 2020)
Amyand´s hernia represents an unusual cause of hernia. It has an incidence of 1% of all inguinal hernias. The clinical presentation depends on the involvement of the hernial sac and the inflammatory state of the appendix. Due to the low frequency of presentation of Amyand's hernia, there is no protocolized treatment. Authors present the case of a 70-year-old patient with the presence of surgically resolved Amyand´s hernia.